2008
DOI: 10.1056/nejmoa0805384
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Rearrangements of Chromosome 1q21.1 and Variable Pediatric Phenotypes

Abstract: BACKGROUND-Duplications and deletions in the human genome can cause disease or predispose persons to disease. Advances in technologies to detect these changes allow for the routine identification of submicroscopic imbalances in large numbers of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
561
2
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 666 publications
(629 citation statements)
references
References 42 publications
40
561
2
17
Order By: Relevance
“…1,2,[5][6][7][8][9][10][11][12] We also examined primary articles and reviews of CNVs in autism, 13 schizophrenia, 14 mental retardation, 15 and congenital heart disease 16 for references to studies reporting subjects with 1q21.1 duplications. [17][18][19][20] Other citations involving 1q21.1 duplication cases were also assessed.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…1,2,[5][6][7][8][9][10][11][12] We also examined primary articles and reviews of CNVs in autism, 13 schizophrenia, 14 mental retardation, 15 and congenital heart disease 16 for references to studies reporting subjects with 1q21.1 duplications. [17][18][19][20] Other citations involving 1q21.1 duplication cases were also assessed.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
“…3,35 We systematically reviewed 28 primary reports identified and their accompanying supplemental materials to identify unique individuals and abstract as much information as possible on each subject. 1,2,[5][6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Any subjects with 1q21.1 duplications that were not 1.0-5.0 Mb (Figure 1) in size were excluded, 12,31 allowing us to include atypical variants that were larger or smaller than the standard duplication classes used in our analyses. We documented the ascertainment criteria, country of origin, authors, and the demographic, clinical, and genotypic characteristics of subjects in different studies, and used these variables to attempt to identify duplicate cases reported in two or more papers.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations